Profil współczesnego turysty pielgrzymkowego = The profile of the contemporary pilgrimage tourist - Aleksandra Katarzyna Ropińska; Zbigniew Podgórski (Kazimierz Wielki University, 2015)
Ropińska Aleksandra Katarzyna, Podgórski Zbigniew. Profil współczesnego turysty pielgrzymkowego = The profile of the contemporary pilgrimage tourist. Journal of Education, Health and Sport. 2015;5(9):227-244. ISSN 2391-8306. DOI10.5281/zenodo.30535 http://dx.doi.org/10.5281/zenodo.30535 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A227-244 https://pbn.nauka.gov.pl/works/619938 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 06.09.2015.   Profil współczesnego turysty pielgrzymkowego The profile of the contemporary pilgrimage tourist   Aleksandra Katarzyna Ropińska, Zbigniew Podgórski   1 Instytut Historii i Stosunków Międzynarodowych, Wydział Humanistyczny, Uniwersytet Kazimierza Wielkiego, 85-067 Bydgoszcz, ul. Jagiellońska 11 czarna91r@interia.pl   2 Instytut Geografii, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego, 85-428 Bydgoszcz, ul. Mińska 15 zbigniew.podgorski@ukw.edu.pl Zakres treści: Celem niniejszego opracowania jest charakterystyka profilu współczesnego turysty pielgrzymkowego. W pracy zasygnalizowano podstawowe kwestie i zagadnienia związane z turystyką pielgrzymkową. Do celów badawczych, użyto metody sondażu diagnostycznego, którego podstawowym narzędziem była ankieta. Badanie przeprowadzono w formie kwestionariusza ankiety internetowej, co pozwoliło na dotarcie do szerokiego grona respondentów. Przyjrzano się dokładnie podstawowym motywom oraz celom podejmowania turystyki pielgrzymkowej. Wskazano najpopularniejsze destynacje turystów pielgrzymkowych w Polsce. Zgodnie z wyznaczonym celem opracowano profil współczesnego turysty pielgrzymkowego. Profil ten, ukazuje swoją przydatność dla organizatorów pielgrzymek, jako obraz oczekiwań potencjalnych klientów. Słowa kluczowe: turystyka kulturowa, turystyka pielgrzymkowa, profil turysty, główne destynacje pielgrzymów, ankieta. Abstrakt: This thesis aimed at creating the profile of the contemporary pilgrimage tourist. The thesis discussed basic issues and questions connected with pilgrimage tourism. The research used the method of diagnostic survey with a questionnaire as a research tool. The research was conducted in a form of an Internet survey questionnaire which enabled the author to reach a great number of respondents. The main reasons for and purposes of making a pilgrimage were scrutinized. The most popular pilgrimage destinations in Poland were mentioned. According to the set objective, the profile of a contemporary pilgrimage tourist was created. The profile may prove useful to pilgrimage organizers as a picture of potential clients' expectations. Keywords: culture tourism, pilgrimage tourism, tourist's profiles, main pilgrimage destinations, questionnaire.